A knowledge-based strategy for renewing a declining industrial city: The Norrkoping way - Peter Svensson; Magnus Klofsten; Henry Etzkowitz (European Regional Science Association (ERSA), 2010)
What the future holds for the industrial cities of the past is a life and death question for many municipalities. Researchers, policy makers and ordinary citizens deal with issues related to developing appropriate strategy for renewing a declining industrial city. Searching the industrial landscape for an existing firm to relocate or establish a branch plant, with an offer of subsidies, is typically the first idea for life support. Developing a new economic base from advanced research is often the next thought for resuscitation. In this paper we study how a small city region, formerly dependent upon old labour-intensive industries, has developed a knowledge-based renewal strategy inspired by ideas emanating from a superseded local economy. Prior research has shown that there are four stages of development in a knowledge-intensive region; inception, implementation, consolidation, and renewal, and at the first stage government and academia take initiative (Etzkowitz & Klofsten, 2005). Later on, the initiative is transferred to industrial actors that identify and exploit the opportunities of the new knowledge. In this process knowledge input is a central aspect of regional development, and stakeholders are active in constructing assets for knowledge production (Cooke & Leydesdorff, 2006; Cooke et al, 2007). We further develop the inception phase of the model through of a triple helix "spaces" strategy for regional renewal, with particular focus in this paper on the consensus space. A longitudinal case study is used to explicate the dynamics of change among university-industry-government actors, including consensus building within the city and with its neighbour city. Our study show that the keys to success were (1) cross-institutional entrepreneurship, aggregating regional and national resources to realize a bespoke locally generated strategy as opposed to the adoption of the usual list of high-tech hot-topics e.g. IT, biotech, alternative energy and (2) striking a balance between intra-regional competition and collaboration in order to achieve common objectives and avoid stasis arising from hyper-competitiveness. Comparisons are made to other relevant cases to infer a theoretical model of regional renewal through hybridization of old and new industrial and knowledge elements.
Keywords: 330; Regional development; triple helix; institutional entrepreneurship; collaboration and competition among city regions